Regional labor markets and the determinants of wage inequality - Topel, Robert (American Economic Review, 1994)
From 1972 to 1990, the United States experienced the largest increase in wage inequality of any developed country. The spread in log wages between the 90th and 10th percentiles of the male wage distribution increased by about 60 points, and inequality increased within virtually every demographic or skill category of the labor force (see Chinhui Juhn et al., 1993). Various explanations have been offered, including changes in the relative demand for skill-intensive goods, international trade, immigration of less-skilled workers, and increased labor-force participation of women. Yet attempts to quantify the relative importance of these factors have not met with much success. This leaves skill-biased change as the residual claimant that rationalizes the data. This paper uses regional differences in the evolution of wage inequality to provide new evidence on the determinants of relative wages. Using a model of factor demand in geographic markets, I isolate contributions of (i) changing skill ratios in the labor force; (ii) increased participation of women; (iii) technical change; and (iv) changes in the industrial composition of labor demand. The data indicate that changing skill ratios and women's labor supply have affected the wages of low-skilled men. In the West, the data indicate that increased immigration of less-skilled Hispanic and Asian workers has adversely affected the wages of natives, causing a greater increase in inequality there than in any other region of the country. I. Modeling Wage Inequality in Regional Markets